Association of Development Disparity, Economic Growth on Poverty in South Sulawesi Province - Imelda Widjaja; Deddy T. Tikson; Rahmadanih (The Journal of Indonesia Sustainable Development Planning, 2022)
The problem of regional development disparity, economic growth and poverty has always been a strategic issue in regional development. Although the direction of the association differs in each region depending on trends in regional development disparity, economic growth and poverty. The purpose of this research is to analyze the association of development disparity between regions, the rate of economic growth to poverty in South Sulawesi Province, with period 2004 – 2019. This study used simple linear regression analysis. The result study is the level of regional development disparity is significant and positively associated with the poverty rate in South Sulawesi. The rate of economic growth has a significant negative association with the poverty rate in South Sulawesi. The variable that has the greatest association with the poverty rate in South Sulawesi Province is the variable of development disparity